Some considerations on the legal regime of the Arctic - Martínez Puñal, Antonio
1. Sovereignty and the incidence of the law of the sea on title to areas and resources; 1.1. The Archipelago of Spitsbergen (Svalbard); 1.2. The Barents Sea; 1.3. Greenland; 1.4. Ellesmere Island; 1.5. Jan Mayen Island; 1.6. The Beaufort Sea; 2. The Arctic as the Common Heritage of Mankind SI